Fear Modulates Visual Awareness Similarly for Facial and Bodily Expressions - Stienen, Bernard M.; de Gelder, Beatrice (Frontiers in Human Neuroscience, 2011)
Background Social interaction depends on a multitude of signals carrying information about the emotional state of others. Past research has focused on the perception of facial expressions while perception of whole body signals has only been studied recently. The relative importance of facial and bodily signals is still poorly understood. In order to better understand the relative contribution of affective signals from the face only or from the rest of the body we used a binocular rivalry experiment. This method seems to be perfectly suitable to contrast two classes of stimuli to test our processing sensitivity to either stimulus and to address the question how emotion modulates this sensitivity. We report in this paper two behavioral experiments addressing these questions. Method In the first experiment we directly contrasted fearful, angry and neutral bodies and faces. We always presented bodies in one eye and faces in the other simultaneously for 60 seconds and asked participants to report what they perceived. In the second experiment we focused specifically on the role of fearful expressions of faces and bodies. Results Taken together the two experiments show that there is no clear bias towards either the face or body when the expression of the body and face are neutral or angry. However, the perceptual dominance in favor of either the face of the body is a function of the stimulus class expressing fear.